Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Từ a+b+c=6 \(\Rightarrow\)a+b=6-c
Ta có: ab+bc+ac=9\(\Leftrightarrow\)ab+c(a+b)=9
\(\Leftrightarrow\)ab=9-c(a+b)
Mà a+b=6-c (cmt)
\(\Rightarrow\)ab=9-c(6-c)
\(\Rightarrow\)ab=9-6c+c2
Ta có: (b-a)2\(\ge\)0 \(\forall\)b, c
\(\Rightarrow\)b2+a2-2ab\(\ge\)0
\(\Rightarrow\)(b+a)2-4ab\(\ge\)0
\(\Rightarrow\)(a+b)2\(\ge\)4ab
Mà a+b=6-c (cmt)
ab= 9-6c+c2 (cmt)
\(\Rightarrow\)(6-c)2\(\ge\)4(9-6c+c2)
\(\Rightarrow\)36+c2-12c\(\ge\)36-24c+4c2
\(\Rightarrow\)36+c2-12c-36+24c-4c2\(\ge\)0
\(\Rightarrow\)-3c2+12c\(\ge\)0
\(\Rightarrow\)3c2-12c\(\le\)0
\(\Rightarrow\)3c(c-4)\(\le\)0
\(\Rightarrow\)c(c-4)\(\le\)0
\(\Rightarrow\hept{\begin{cases}c\ge0\\c-4\le0\end{cases}}\)hoặc\(\hept{\begin{cases}c\le0\\c-4\ge0\end{cases}}\)
*\(\hept{\begin{cases}c\ge0\\c-4\le0\end{cases}\Leftrightarrow\hept{\begin{cases}c\ge0\\c\le4\end{cases}\Leftrightarrow}0\le c\le4}\)
*
\(a^3+b^3\le ab\left(a+b\right)\) (1)
\(\Leftrightarrow a^3+b^3-ab\left(a+b\right)\le0\)
\(\Leftrightarrow\left(a+b\right)\left(a^2-ab+b^2\right)-ab\left(a+b\right)\le0\)
\(\Leftrightarrow\left(a+b\right)\left(a^2-2ab+b^2\right)\le0\)
\(\Leftrightarrow\left(a+b\right)\left(a-b\right)^2\le0\)
Vì \(a\le0;b\le0\Rightarrow a+b\le0;\left(a-b\right)^2\ge0\forall a;b\)
\(\Rightarrow\left(a+b\right)\left(a-b\right)^2\le0\forall a;b\le0\)
\(\Rightarrow\) BĐT (1) luôn đúng \(\forall a;b\le0\)
Vậy \(a^3+b^3\le ab\left(a+b\right)\)
\(C=\frac{1}{a^2+b^2}+\frac{1}{2ab}+ab+\frac{16}{ab}+\frac{17}{2ab}\)
\(C\ge\frac{4}{a^2+b^2+2ab}+2\sqrt{ab.\frac{16}{ab}}+\frac{17}{\frac{2\left(a+b\right)^2}{4}}\)
\(C\ge\frac{4}{\left(a+b\right)^2}+8+\frac{34}{\left(a+b\right)^2}\ge\frac{4}{4^2}+8+\frac{34}{4^2}=\frac{83}{8}\)
Dấu "=" khi \(a=b=2\)
Lời giải:
a)
$a+b+c=0\Leftrightarrow (a+b+c)^2=0$
$\Leftrightarrow a^2+b^2+c^2+2(ab+bc+ac)=0$
$\Rightarrow ab+bc+ac=-\frac{a^2+b^2+c^2}{2}\leq 0$
Mà $a^2\geq 0$
Do đó: $a^2(ab+bc+ac)\leq 0$
$\Leftrightarrow a^3b+a^2bc+a^3c\leq 0$ (đpcm)
Dấu "=" xảy ra khi $a=0$
b)
Từ ĐKĐB \(\Rightarrow \left\{\begin{matrix} a+b=(3c+3)\\ 4ab=9c^2\end{matrix}\right.\)
Ta biết rằng $(a+b)^2=(a-b)^2+4ab\geq 4ab$
$\Leftrightarrow (3c+3)^2\geq 9c^2$
$\Leftrightarrow (c+1)^2\geq c^2$
$\Leftrightarrow 2c+1\geq 0\Leftrightarrow c\geq \frac{-1}{2}$ (đpcm)
Vậy.......
\(ab+2bc+3ac\)
\(=ab+2bc+ac+2ac\)
\(=a\left(b+c\right)+2c\left(a+b\right)\)
\(=-a^2-2b^2\le0\) (đúng)
Dấu "=" khi \(x=y=z=0\)
\(x=y=z=0?\)